PENGARUH MODEL PEMBELAJARAN MAKE AND MATCH TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA DI KELAS III SD NEGERI 89 PALEMBANG - Yogi Aditiya Prasetyo; liza murniviyanti; Eni Heldayani (STKIP Subang, 2023)
This study aims to determine the effect of the make and match learning model on student learning outcomes on energy sources in class III at SD Negeri 89 Palembang. The population of this study were all 39 students in class III and the sample used a saturated sample consisting of 2 classes, namely the experimental class, which consisted of 20 students and the control class, which consisted of 19 students. The author applies the make and match learning model in the experimental class through the direct learning model in the control class. The research instrument used by researchers is a multiple choice test. Based on the calculation of the hypothesis test, the posttest value for the experimental class and control class was 4.614 with a value of t_table = 1.687 and df = n - 2 where n = 39 so df = 37. So it can be concluded that t_count = 4.614 ≥ t_table = 1.687, thus H_0 is rejected and H_a is accepted or there is an influence of the make and match learning model on student learning outcomes in science subjects in class III SD Negeri 8 9 Palembang. Keywords: Make And Match Learning, Learning Outcomes.